ANALISIS KUALITAS PELAYANAN DAN KEPUASAN SERTA PENGARUHNYA PADA LOYALITAS NASABAH (Studi pada PT. BPR Berkah Pakto Kediri) - Ditsar Nauful Widi Putra (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The type of this research is descriptive research and explanatory research is a study that describes the problems of the current facts of a population and said explanatory research because this study explains the position of the variables studied and the relationship between one variable with another. This research uses random sampling technique in sampling as many as 109 people as respondents. Measurement scale using Likert scale with five choices of answers. This research uses descriptive analysis technique and multiple regression analysis. Based on the result of data analysis, it can be concluded that (1) Quality of Service (X1) has a positive and significant effect on customer loyalty of PT.BPR Berkah Pakto, while Satisfaction (X2) has positive and significant impact on customer loyalty of PT.BPR Berkah Pakto; (X1.1), Reliability (X1.2), Responsiveness (X1.3), Guarantees (X1.4), Empathy (X1.5) have a positive and significant influence on customer loyalty of PT .BPR Berkah Pakto (Y). (3) The independent variable gives effective contribution to customer loyalty of PT. BPR Berkah Pakto is a service quality and customer satisfaction of 38.4%, the rest is influenced by other variables.The researcher's suggestion is expected for further researcher to find or examine other variables outside of this research, because customer loyalty is also influenced by other variables. The variable is like the value felt by the customer, because the variable also affects customer loyalty.